Politicking for Postwar Modernism: The Architectural Research Group of Ottawa and Montreal - Valen, Dustin (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2017)
The diffusion of modernist principles in Canadian building and planning occurred through many channels, but among these the Architectural Research Group of Ottawa and Montreal played a crucial role. Formed in 1938 to conduct research into postwar reconstruction, the group produced articles, radio addresses, and exhibitions in an effort to nurture modernist sentiment across the country. For these young architects, the federal government’s commitment to replanning and rebuilding postwar Canadian cities presented them with an opportunity to intervene in the future of Canadian practice. They decried the “backwardness” of conservative practitioners while promoting the ideas of a European avant-garde and orchestrating numerous transatlantic exchanges. This article discusses the group’s role in politicking for architectural and urban modernism, as well as the contributions of some of its key members. It shows that Canadian professionals were not simply passive receptors of international modernism but played an active part in shaping these ideas during the immediate postwar period, and that Canada’s federal government played a unique role in accelerating this process by allowing modernist architects and planners to operate within and through a number of government-sponsored agencies.